LAND SUBSIDENCE AND GEOTECHNICAL IMPACT OF JAKARTA KOTA AREA - Irfan Marwanza; Afiat Anugrahadi; Untung Sumotarto; Riskaviana Kurniawati; Himmes Fitra Yuda; Rosmalia Nugraheni (Universitas Trisakti, 2023)
Land subsidence has long occurred around the Special Capital Region of Jakarta. It is important to know and deal with Land subsidence events which also cause various negative impacts. Aim: When large amounts of groundwater are withdrawn from certain types of rocks, such as fine-grained sediments, land subsidence occurs. The rock compacts because the water helps to keep the ground in place. When the water is removed, the rocks collapse in on themselves.The immediate impact is the building collapse around the Kota Tua of DKI Jakarta. Methodology and Results: The research method used is a quantitative descriptive survey method by observing the amount of land subsidence that occurs in the Kota Tua area and its surroundings. The results showed that there has been a vertical land subsidence that varies between 20-60 cm. Based on the results of the resistivity values and coordinates plotted on the Regional Geological Map (Jakarta and Kep Seribu), the research location is classified into Lithology: Clay, Sand Silt, Gravel, and Pebbles (Quartenary deposits). The phenomenon, land subsidence, is caused by a combination of various parameters, including natural consolidation of alluvial soils, excessive groundwater extraction, and also building loads from infrastructure development and tectonic factors. Conclusion, significance, and impact study: Knowing the value of land subsidence and its location is expected to support urban planning, basic infrastructure planning and development, housing, settlement planning, and local financial improvement in efforts to mitigate land subsidence disasters.